Hinterland : the imaginative reanimation of Brixton cemetery's nostalgic, remnant reality through the mechanization of its inherent narrative of escape - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2018)
Mini Dissertation MArch (Prof)--University of Pretoria, 2018.